Gender differences in rice value chain participation and career preferences of rural youth in India - Veettil, Prakashan Chellattan; Raghu, P.; Mohapatra, B.; Mohanty, Samarendu (Informa UK Limited, 2021)
Ageing farming communities and youth abandoning agriculture are serious issues, with attracting and retaining youth in agriculture a key challenge. This article reports on a gender-sensitive study of rural youth conducted in eastern India. The willingness to be involved in agriculture varies across region and gender, with the high readiness of female youths signalling a feminisation in agriculture. Involvement in value chain activities has a significant and positive impact on career choice. Youth policy needs to address the different preferences and facilitation requirements of male and female youth, in order to change youth’s aspiration and be inclusive of both genders.